Financial management practices predicting participation of family in risky asset - Abdul Rahim @ Abdul Wahab, Husniyah; Abdul Samad, M. Fazilah (2012)
In pursuing high expected return from investment, families are willing to sacrifice the high expected risk associated with stock. This study is designed to focus on the ability of financial management practices to predict participation of Malaysian family in risky asset. Micro-data are obtained through questionnaire responses and self-administered by 800 family financial managers. Quota sampling used a ratio of 60 to 40 for the urban and rural areas in Peninsula Malaysia. Information on socio-economic characteristics, time orientation, risk preference and financial management practices are gathered. Stock is taken as risky asset, thus family participating in stock is said to participate in risky assets. Results from binary logistic regression revealed that for the likelihood to participate in risky asset, a family saves more for short-term and long-term financial needs, and purchases insurance to overcome various financial risks. However, doing record-keeping does not predict much of the occurrence of participation in risky assets. Credit practices construct is inversely predicting the probability to invest in risky asset. Hence, families participating in risky assets performed other financial practices to hedge against financial risks. Consumers themselves should ensure that they are financially prepared via high liquidity in terms of savings and managing risk appropriately to cushion them from financial losses. Their financial preparedness would most probably lead to enhanced wellbeing, financially and psychologically.